Clinical and Prognostic Effect of Plasma Fibrinogen in Renal Cell Carcinoma: A Meta-Analysis. (5th January 2017) - Tian, Yuejun; Hong, Mei; Jing, Suoshi; Liu, Xingchen; Wang, Hanzhang; Wang, Xinping; Kaushik, Dharam; Rodriguez, Ronald; Wang, Zhiping
Abstract : Background . Although numerous studies have shown that plasma fibrinogen is linked to renal cell carcinoma (RCC) risk, the consistency and magnitude of the effect of plasma fibrinogen are unclear. The aim of the study was to explore the association between plasma fibrinogen and RCC prognosis. Methods . An electronic search of Embase, PubMed/MEDLINE, and the Cochrane databases was performed to identify relevant studies published prior to June 1, 2016. Results . A total of 3744 patients with RCC from 7 published studies were included in the meta-analysis. The prognostic and clinical relevance of plasma fibrinogen are evaluated in RCC patients. Statistical significance of the combined hazard ratio (HR) was detected for overall survival, cancer-specific survival, and disease-free survival. Our pooled results showed that elevated plasma fibrinogen was significantly associated with clinical stage and Fuhrman grading. The level of plasma fibrinogen was not found to be associated with tumor type and gender. Conclusions . Elevated plasma fibrinogen is a strong indicator of poorer prognosis of patients with RCC, whereas the plasma fibrinogen is not significantly associated with tumor type. Therefore, plasma fibrinogen could be used in patients with RCC for risk stratification and decision providing a proper therapeutic strategy.